A Comparative Analysis on the Role and Market Linkages of Gold Backed Assets During COVID-19 Pandemic - Sruthy Madhavan; S. Sreejith (Scientific Annals of Economics and Business)
Gold is a traditional favorite investment avenue for investors all over the globe, particularly during the crisis period. Irrespective of the nature of the crisis, investors are allocating their funds to different gold-backed assets. This paper uses various globally traded gold-backed assets to identify its role and market linkages during the Covid 19 pandemic. Daily prices of assets from March 2020 to January 2022 were employed. DCC GARCH model is used to ascertain time-varying correlations and quantile regression was employed to examine the relationship between assets in different quantiles. Based on the analysis, safe haven property of all the assets is revealed and it is associated with the severity of the stock market crash as specified by the quantiles. Moreover, double exposure of gold mining stock results in different flights to quality. Co-movement of gold bullion, gold futures, and gold volatility index is visible during this crisis. Gold Exchange Traded Funds and gold-backed cryptocurrency offer diversification by decoupling with gold bullion in the portfolio. The paper highlights the importance of the choice of gold-backed assets along with gold bullion in the investment portfolio based on its role and market linkages.